Lingkungan Pendidikan dalam Perspektif Al-Qur’an - Supian Munawar; Syamsul Maarief; Badruzaman Badruzaman; Endi Suhendi (Simpati, 2026)
The research in this paper aims to explore the concepts and principles of the educational environment from the perspective of the Qur'an and Hadith using a tafsir tarbawi (educational exegesis) approach. The developmental dynamics of human potential, both spiritual and intellectual, do not occur in a vacuum but are heavily influenced by environmental factors (educational ecology). By employing textual, thematic, and contextual analysis methods on several key verses such as QS. Al-Alaq: 1-5, QS. At-Tahrim: 6, QS. Luqman: 13-19, QS. Al-Kahfi: 66-70, and QS. Al-Hujurat: 13 this study maps the Islamic educational ecosystem into several primary domains. The results of the analysis indicate that the Qur'an constructs the educational environment as an integrative macro-systemic unity, comprising the domestic family environment (as a fortress for moral and creedal protection), the formal academic school/pesantren environment (as a space for teacher-student etiquette and ethics), and the socio-communal environment (as an arena for egalitarian multicultural inclusivity). Furthermore, this study formulates five fundamental paradigms of Islamic educational ecology: the integralistic, tawhid (monotheistic), humanistic-egalitarian, gradual-systemic, and transformational-emancipatory paradigms. This theoretical reconstruction corrects Western secular empiricism while simultaneously providing a holistic foundation for educators in managing an educational environment that aligns with divine revelation values and the demands of modern civilization.